1997
DOI: 10.1046/j.1365-2133.1997.19472062.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with psoriasis: the contribution of clinical variables and psoriasis-specific stress

Abstract: The purpose of this study was: (i) to examine the impact of the clinical severity, anatomical location and treatment of psoriasis on patients' quality of life, and (ii) to investigate the effects of perceptions of psoriasis-related stress on patients' physical and mental health and on areas of disability in everyday life. All patients (n = 204) attending a psoriasis specialty clinic were invited to complete a multidimensional quality of life assessment comprising the Psoriasis Disability Index (PDI), the SF-36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
128
4
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(157 citation statements)
references
References 17 publications
20
128
4
5
Order By: Relevance
“…10-14 Few studies in the literature show similar results and give support to those found in the present investigation. 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…10-14 Few studies in the literature show similar results and give support to those found in the present investigation. 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis influences significantly the health-related quality of life (HRQoL) issues, including the physical, psychological and social facets of the patient’s life 56,57. For this reason, as proved by different studies, the treatment with infliximab is effective even on patient QoL.…”
Section: Infliximab Quality Of Life and Nail Involvementmentioning
confidence: 99%
“…In studies directed to treatment of special sensitive skin areas modified PASI or target area scores (TAS) were employed. Some studies included an evaluation of patients’ quality of life during treatment using the psoriasis disability index (PDI) or quality of life (QOL) questionnaires about daily activities 31,32…”
Section: Clinical Studies – General Methodologymentioning
confidence: 99%